Charles Booth's London : a portrait of the poor at the turn of the century drawn from his Life and labour of the people in London - Booth, Charles; Fried, Albert; Elman, Richard M.; Williams, Raymond (London: Penguin Books, 1971)
"Charles Booth ; selected and edited by Albert Fried and Richard M. Elman ; foreword by Raymond Williams Bevat een selectie uit 'Life and labour of the people of London' (Booth, Charles)"